Performance of Sclerodermus brevicornis, a parasitoid of invasive longhorn beetles, when reared on rice moth larvae. Issue 1 (5th July 2020) - Abdi, Mohamed Khadar; Jucker, Costanza; De Marchi, Beatrice; Hardy, Ian C.W.; Lupi, Daniela
Abstract: Biological control efficiency can be improved by developing effective mass‐rearing systems to produce large numbers of high‐quality parasitoids. This study explored an alternative host for rearing Sclerodermus brevicornis (Kieffer) (Hymenoptera: Bethylidae), a potential biocontrol agent for the suppression of exotic and invasive wood‐boring longhorn beetle (Coleoptera: Cerambycidae) populations in the European agroforestry ecosystems. We tested larvae of the rice moth, Corcyra cephalonica Stainton (Lepidoptera: Pyralidae), as host for the parasitoid. We quantified the probability and timing of host attack and parasitism as well as reproductive success, offspring production, and the characteristics of adult offspring. As S. brevicornis is a quasi‐social species (multiple females, communally produced offspring broods), we also explored the effects of varying the number of females to which individual hosts were presented, with the aim of determining the optimal female‐to‐host ratio. As time to host attack can be a limiting factor in S. brevicornis rearing protocols, we tested the use of adult females of another bethylid species, Goniozus legneri Gordh, to paralyse C. cephalonica larvae prior to presentation. We identified the conditions within our experiment that maximized offspring production per host and offspring production per adult female parasitoid. We found that C. cephalonica is suitable as a factitious host and, as it is considerably more straightforward for laboratory rearing than cerambycid species, it is a good candidate for adoption by future S. brevicornis mass‐rearing and release programmes. Abstract : This study explored the use of the factitious host Corcyra cephalonica (Lepidoptera: Pyralidae) for rearing Sclerodermus brevicornis (Hymenoptera: Bethylidae), a potential biological control agent of exotic and invasive wood‐boring longhorn beetles (Coleoptera: Cerambycidae) in the European agroforestry ecosystems. As S. brevicornis is a quasi‐social species (multiple females, communally produced offspring broods), we also explored the effects of varying the number of females to which individual hosts were presented, with the aim of determining the optimal female‐to‐host ratio.